Women in new migrations current debates in European societies - Slany, Krystyna; Kontos, Maria; Liapi, Maria (Jagiellonian University Press, 2010)
The volume Women in New Migrations: Current Debates in European Societies offers an overview of research and debates concerning new female migrants in European countries. Despite the effects of globalisation and the Europeanisation both of national migration and integration policies and of studies carried out by transnational research projects, social, economic and political conditions at a national level remain a powerful basis of academic production. Varying conditions for migration and integration and language and cultural specificities create differentiated research and debates